Corporate Governance and Accountability of Financial Institutions - Akuffo, Jonas Abraham. author. aut Link
XXIII, 412 p. 81 illus., 77 illus. in color.
Keywords: The presence of sound corporate governance in a financial institution is important in maintaining the confidence of both the market and the public. The power that corporate governance holds over the success of some of the largest financial institutions in the world is not to be downplayed. This book methodically assesses the quality of corporate governance and mechanisms of accountability disclosures to various stakeholders. It is further intended to provide fresh insights into some specific corporate governance recommendations to help improve good governance in financial institutions, particularly in the United Kingdom and the EU but will also be applicable to other major economies. It explores what, when and how corporate governance has changed the financial institution functions and corporate executive behaviour by critically reviewing the pre- and post-financial crisis theoretical and empirical literature. Increasingly driven by the nature of complications, complexities and opacity in the operations of financial systems, corporate governance reporting plays an important role in the financial sector. It will provide insights into corporate governance disclosures over a long-term basis. This book should be a valuable asset to support the research of practitioners, students and all academics due to its stimulating and reflective insights into this fascinating topic. Jonas Abraham Akuffo is trained finance and business management expert, is currently working in strategic finance and pricing in the healthcare industry. He holds a Joint Doctor of Business Administration in Accounting & Finance, an MBA in Finance, a master’s in Business Economics, Finance & Banking, a BA in Economics and has completed his studies in Ghana, England and France. He is also a Fellow of Chartered Management Institute (FCMI). His current research interests include accountability, corporate governance, healthcare financing, strategic corporate finance and management control systems.